2013
DOI: 10.4236/cweee.2013.22b002
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Contamination of Drinking Water in the Internally Displaced People Camps in South Darfur, Sudan

Abstract: A total of 240 water samples were collected during the three seasons of 2009 from different sites and sources in the internally displaced camps (IDP) including bore holes, hand pumps, dug wells, water points, water reservoir and household storage containers. Samples were investigated using the most probable number method to detect and count the total coliform, faecal coliform and faecal enterococci. Enteric bacteria detected were E. coli, Enterococcus faecalis, Klebsiella, Citrobacter and Enterobacter .House h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 1 publication
2
3
0
Order By: Relevance
“…Similarly, in the present study, the majority of samples from water sources (springs and dug well) were positive for faecal coliforms. This study finding in agreement with studies conducted in South Darfur, Sudan and Vina Division, Adamawa, Cameroon by Mohammed Eltahir et al 17 and Viban et al 23 respectively. The reason for contamination with faecal coliforms may be resulted from a lack of fence around the spring and dug well and animals could easily access.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Similarly, in the present study, the majority of samples from water sources (springs and dug well) were positive for faecal coliforms. This study finding in agreement with studies conducted in South Darfur, Sudan and Vina Division, Adamawa, Cameroon by Mohammed Eltahir et al 17 and Viban et al 23 respectively. The reason for contamination with faecal coliforms may be resulted from a lack of fence around the spring and dug well and animals could easily access.…”
Section: Discussionsupporting
confidence: 93%
“…This finding is in line with the study conducted on a similar setting (IDP site) in South Darfur, Sudan. 17 This might be due to poor hygiene and sanitation practices around water sources causes’ faecal contamination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For such prevalent illnesses that are associated with heavy morbidity, and yet largely preventable, it was quite unclear why those underdeveloped countries have not widely adopted a simple, cost-effective, and highly efficient approach as chlorination [ 9 , 10 ] that has been around for decades. This is pretty much in line with the findings of Eltahir et al [ 11 ] study that was the first of its kind to investigate the outcome of treating drinking water with chlorine in IDP and refugees camps in Sudan.…”
Section: Discussionsupporting
confidence: 85%
“…The data provided hereinbefore demonstrate how pervasive waterrelated ailments are in urban centers in the country [18][19][20]. Other studies have shown that the situation is even worse in refugee camps, yet none has investigated whether conventional intervention would work in the special settings of Sudanese refugee camps [21]. Our study questioned whether tanks' chlorination, rather than home treatment, would provide a meaningful measure to control waterborne diseases in settlements that were established long time ago.…”
Section: Introductionmentioning
confidence: 93%